PRODUCTION AND OPTIMIZATION OF L-GLUTAMINASE FROM MANGROVE ISOLATE AND COMPARATIVE MUTATIONAL STUDIES - D. DIVYA TEJA,; V. SRIDEVI,; N. HARSHA,; A. SWATHI, (International Journal of Pharma and Bio Sciences, 2016)
Actinomycetes, isolated from marine and mangrove sediment samples, were evaluated for the production of L-glutaminase. All the isolates were screened for L-glutaminase production and the one exhibiting maximum glutaminolytic activity was selected as potential L-glutaminase producer and used for mutational studies. Both wild and mutant strains were used for L-glutaminase production by solid state fermentation using different agro- industrial by-products such as green gram, black gram, coconut oil cake, sesame oil cake, rice bran and wheat bran. Sesame oil cake was the best substrate for induction of L-glutaminase (153.066 U/gds by wild strain and 158.53 U/gds by mutant strain). Culture conditions like initial moisture content, inoculum volume, temperature and pH of the culture medium were optimized using a 24 full factorial CCD (Central Composite Design) and a second order polynomial model equation was obtained. The predicted optimum levels were as follows: temperature 36.210C, inoculum volume 1.87 ml, initial moisture content 69.47 % (v/w) and pH 8.2. Under these optimum conditions, the experimental yield of L-glutaminase was 203.86 U/gds, which was in close agreement with the value predicted by the model, 206.57 U/gds. In the present study the value of the regression coefficient R2 = 0.9894 which indicates that 98.94% of the variability in the response could be explained by the model.